Prunus padus L. as a source of functional compounds – antioxidant activity and antidiabetic effect - Telichowska, Aleksandra; Kobus-Cisowska, Joanna; Cielecka-Piontek, Judyta; Sip, Szymon; Stuper-Szablewska, Kinga; Szulc, Piotr (Emirates Journal of Food and Agriculture, 2022)
The search for natural raw materials and their beneficial properties has recently become very popular. Bird cherry (Prunus padus L.) is a plant that grows mainly in Europe. The properties of its individual anatomical parts stem from the content of numerous characteristic compounds. The aim of the paper was to assess the impact of the way of bird tree (P.padus) fruit and bark extraction on the antioxidant potential and the assessment of inhibitory activity against alpha-glucosidase, catalase and glutathione reductase and peroxidase. Bark extract had a greater antioxidant potential. The highest chelating activity was determined for acetone-water extract of black cherry bark (44.87%), and ethanolic bark extract showed the highest reducing power. These activities, however, were similar for all extracts tested. It was demonstrated that ferulic acid and gallic acid predominated among polyphenols in aqueous extracts, together with quercetin and catechin, whose presence and proportion of occurrence probably determined the inhibitory activity against alpha-glucosidase, whose activity for fruit extract was determined at the level of 27.11 IC50 mg/ mL.